ANALYSIS OF THE DESIGN FEATURES OF BULK CARRIER FLEET VESSELS AS A PREREQUISITE FOR STUDYING THE ACTIVITIES OF WELDERS - OSTAPENKO, NATALIA; KUZNETSOVA, POLINA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
This article analyzes the characteristics of various dry bulk carriers, which are among the most prevalent types in modern global maritime shipping. Drawing upon data from various sources, the study determines their position within the overall structure of the civil fleet. The varieties of dry bulk carriers are generalized based on their cargo capacity, dimensions, cargo type, and design features. Particular attention is given to design features and their operational conditions in commercial sea passages. The most common bulk carriers used for transporting bulk cargo are identified. Graphic and descriptive representations of the ship’s general structure and hull are provided. The functional systems of ship pipelines, designed for conveying various substances, are presented. The main materials employed in the construction of the hull, superstructures, hatch covers, mechanisms, equipment, and ship piping systems, with low-carbon steel being key, are outlined. The significance of regular repair and maintenance to ensure the good condition of the main components of bulk carriers and the reliable transportation of goods is emphasized. It is confirmed that a substantial portion of their repair work involves welding operations. This analysis will subsequently facilitate a more comprehensive description of the activities of ship welders. The ship’s piping system is clearly shown with various substances on board, including sea water, oil, gas, steam, fuel, fresh water, sewage, ballast water, etc. to perform specific functions. The main materials used to make the hull, superstructures, hatch covers, mechanisms, equipment and pipelines on ships are listed. It was emphasized that a significant amount of repair activity on bulk carriers is related to welding work, which plays a crucial role in keeping the vessel operational throughout its entire service life.